The Predictive Effect of Preschool Children's Temperament Characteristics and Parenting Styles of Mothers on Ego Resiliency Level of Children - (:unkn) unknown (TURKISH EDUCATION ASSOC, 2018)
The aim of the study is to investigate the predictive effect of the temperament charecteristics of preschool children and their mothers' parenting styles on ego resiliency level of children. The study was designed in survey method. The sample of the study was selected by random sampling method from central districts of Istanbul, Turkey. The sample consists of 367 children in total and 198 (54%) of these children are girls and 169 (46%) of them are boys. Demographic Information Form, Children's Ego Resiliency Scale, Short Temperament Scale for Children and Parenting Styles and Dimensions Questionnaire were used to collect data. The data was collected during fall semester in 2015-2016 academic year. Multiple regression analyses were used to test the relation between childrens's ego resiliency level, temperament charecteristics and their parents' parenting styles. Authoritarian and permissive parenting styles and persistence and reactivity traits of temperament together explained 33% of the variance in ego resiliency and the relation between these variables was found to be as moderate (r = 0.58, p<0,05). The authoritarian parenting style among other explanatory variables is the most powerful variable on ego resiliency of children and these variables are inversely related.
Keywords: Preschool period; Ego resiliency; Temperament; Parenting styles; Multiple regression analysis; EFFORTFUL CONTROL; PROSOCIAL BEHAVIOR; SOCIALIZATION; EMOTIONALITY; COMPETENCE; CHILDHOOD; STRESS